Tuberculosis cases comparison in developed country (Australia) and developing country (Indonesia): a comprehensive review from clinical, epidemiological, and microbiological aspects - Ni Luh Putu Harta Wedari; I Wayan Adi Pranata; Ni Nyoman Sri Budayanti; I Dewa Made Sukrama (Intisari Sains Medis, 2021)
Background: Tuberculosis (TB) is one of most crucial public health issues around the world. TB is an entity of a complex disease with the socio-economic aspect that has very strong correlation in regard to combat this disease. Migration from developing country to developed country inevitably possesses big influence on global epidemiologic of TB. In Australia, TB still becomes the main threat not only in native population but also regarding the migrant movement into Australia. Indonesia is one of among the TB endemic countries with high TB cases, in which not merely due to its high TB prevalence and incidence but also influenced by very high and dense population.Aim: This literature aims to review the clinical, epidemiological, and microbiological aspects of tuberculosis as a comparison between developed country (Australia) and developing country (Indonesia).Conclusion: Tuberculosis cases in Australia remains low compared to Indonesia, however, the close proximity to adjacent developing countries with high endemic of TB contributes significantly to increase number of TB in Australia. Tuberculosis can be cured by following the treatment guidelines with proper monitoring. Moreover, the collaboration between public and private sector along with active collaboration from the family or people surrounding the patients is required to eliminate TB disease.